2022
DOI: 10.3390/biology11020225
|View full text |Cite
|
Sign up to set email alerts
|

MOET Efficiency in a Spanish Herd of Japanese Black Heifers and Analysis of Environmental and Metabolic Determinants

Abstract: Multiple ovulation and embryo transfer (MOET) systems have been intensively implemented in Japanese Black cattle in Japan and to create Japanese Black herds out of these areas. Environmental conditions influence MOET efficiency. Thus, we describe results of 137 in vivo, non-surgical embryo flushings performed between 2016–2020, in a full-blood Japanese Black herd kept in Spain and the possible effects of heat, year, bull, donor genetic value, and metabolic condition. Additionally, 687 embryo transfers were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
1
0
0
Order By: Relevance
“…Neither feeding frequency nor gluconate supplementation significantly or clearly affected any of the reproductive indices that we examined, and the values in our study were similar to those reported for heifers on commercial farms in other European countries and USA [20,61,62] which have been associated with efficient rearing [20,63,64]. Consistently with this, we found that levels of total cholesterol as well as low-and high-density lipoprotein were within physiological ranges for prepubertal calves and pubertal heifers [65][66][67], suggesting healthy follicle growth and good reproductive performance in the future [68].…”
Section: Discussionsupporting
confidence: 89%
“…Neither feeding frequency nor gluconate supplementation significantly or clearly affected any of the reproductive indices that we examined, and the values in our study were similar to those reported for heifers on commercial farms in other European countries and USA [20,61,62] which have been associated with efficient rearing [20,63,64]. Consistently with this, we found that levels of total cholesterol as well as low-and high-density lipoprotein were within physiological ranges for prepubertal calves and pubertal heifers [65][66][67], suggesting healthy follicle growth and good reproductive performance in the future [68].…”
Section: Discussionsupporting
confidence: 89%
“…The average of total embryos obtained in our study was 7.8, which is in close agreement with Vázquez-Mosquera et al (2022). However they found average viable embryos to be 7.1, whereas in our study it was only 4.8.…”
Section: Materials a N D Methodssupporting
confidence: 90%